Evolution of effective thermal conductivity during hydrate formation and decomposition in natural sediments. (February 2019) - Wei, Rupeng; Yang, Lei; Zhao, Jiafei; Wang, Ji; Wang, Youle; Ling, Zheng; Li, Yanghui; Yang, Mingjun; Song, Yongchen
Abstract: Gas hydrates are regareded as a potential alternative energy sources for sustainable development. Thermal properties of gas hydrate-bearing sediments directly govern the heat transfer process during hydrate decomposition which couples with phase transitions and multiphase flows. Latest database on the thermal properties of natural sediments containing gas hydrates still remains limited. Here we report on point heat source measurements of the effective thermal conductivity of hydrate-bearing sediments through a thermistor-based method and evaluation of existing models. Effective thermal conductivity of water saturated natural sediments and partially saturated hydrate-sediment are obtained, showing a significant effect of compaction on the effective thermal conductivity of the sediments. The evolution of thermal conductivity during hydrate formation, decomposition and reformation indicates that the variation of the components in the pores could play a crucial role in the effective thermal conductivity. A higher saturation of hydrates in the pores and a smaller porosity could contribute to a better thermal conductivity. The evolution of the effective thermal conductivity with hydrate formation and decomposition also demonstrates a temperature dependence. Moreover, the reformation process after hydrates are fully decomposed significantly impacts the variation of the effective thermal conductivity, which could be attributed to the solution migration during decomposition and the local inhomogeneity of hydrate reformation. The slightly increase in the thermal conductivity below zero degree Celsius implies the small fraction of ice generation during the cooling process. The results could provide some insights into the effect of hydrate formation and decomposition on the effective thermal conductivity of natural sediments, which would be helpful in the heat transfer evaluation and gas production simulation in the field test.